Psychological Impact of Poverty Alleviation through Resettlement Programmes: Special Reference to Young Adult Women Resettlers in Sri Lanka - Perera, Niroshan; Karunathilake, K. (Technium Social Sciences Journal, 2023)
Resettlement as a poverty alleviation strategy is common in Sri Lanka. Many local and international entities along with the government, relocate poor people with better housing facilities and uplift their living standards. Especially, providing a new housing unit with basic facilities is making them a favorable atmosphere to nurturing a new livelihood pattern, new social network system, access to market, access for school and health facilities, etc. However, there are many negative consequences of resettlement, particularly relating to the mental health and psychological well-being of resettlers. It is also revealed that women are more vulnerable to resettlement and experience many mental health issues during and after resettlement. In addition, there are several psychological impacts among the resettlers that have been identified apparently. However, no detailed study to date has directly focused on the main contributions to the mental health of women resettlers in Sri Lanka. This study aimed to address said gap from a sociological perspective with reference to popular resettlement models, concepts, and other related frameworks. Particularly, this study is focused in Kaluthara district of Sri Lanka. The study revealed that resettled woman usually go through a transition period where she experience emotional disturbances such as fear, anxiety and stress which gradually reduces when she adjusts to the new environment, if resettlement initiative assures,financial strength with better livelihood opportunities and social recognition. Also, study findings conclude how resettlers could experience mental and emotional instability due to lack of essential facilities like proper sanitation, efficient public services, better safety and security, corporative and pleasant neighborhood etc.